2017
DOI: 10.1016/j.jconrel.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal vaccination with hollow microneedles: A comparative study of various protein antigen and adjuvant encapsulated nanoparticles

Abstract: In this study, we investigated the potential of intradermal delivery of nanoparticulate vaccines to modulate the immune response of protein antigen using hollow microneedles. Four types of nanoparticles covering a broad range of physiochemical parameters, namely poly (lactic-co-glycolic) (PLGA) nanoparticles, liposomes, mesoporous silica nanoparticles (MSNs) and gelatin nanoparticles (GNPs) were compared. The developed nanoparticles were loaded with a model antigen (ovalbumin (OVA)) with and without an adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 48 publications
0
93
0
Order By: Relevance
“…This study showed that nanoparticles coated with poly lactic-co-glycolic acid (PLGA) induced a stronger IgG2a response than mesoporous silica nanoparticles, gelatin nanoparticles and liposomes. Moreover, CD8 + and CD4 + T cell responses were highest when induced by OVA/poly(I:C)loaded liposomes [28]. In summary, a microneedle delivery method was suggested for the intradermal injection of nanoparticle vaccines.…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 93%
See 1 more Smart Citation
“…This study showed that nanoparticles coated with poly lactic-co-glycolic acid (PLGA) induced a stronger IgG2a response than mesoporous silica nanoparticles, gelatin nanoparticles and liposomes. Moreover, CD8 + and CD4 + T cell responses were highest when induced by OVA/poly(I:C)loaded liposomes [28]. In summary, a microneedle delivery method was suggested for the intradermal injection of nanoparticle vaccines.…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 93%
“…In summary, a microneedle delivery method was suggested for the intradermal injection of nanoparticle vaccines. This novel antigen administration approach was tested in murine models [28]. However, it may induce tolerance more efficiently in human compared to other administration routes.…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
“…Antigen co-encapsulated with adjuvant induced antibody responses in a more effective way compared with the free OVA/adjuvant. This demonstrated that hollow MNs accompanied by the applicator are a promising tool for intradermal vaccination [74]. Using the same liposome composition and the co-encapsulation of diphtheria toxoid and adjuvant, it was demonstrated that cationic liposome is able to initiate strong immune responses.…”
Section: Hollow Mnsmentioning
confidence: 96%
“…Much attention has been focused on the P. aibuhitensis in recent years because several bioactive components have been identified from P. aibuhitensis including antimicrobial peptide (Pan, 2004), glycerophospholipids (Hirobe et al, 2015) and protease (Li et al, 2006), etc. Owing to P. aibuhitensis good adaptability to stressful environmental conditions, some researchers have regarded them as biochemical responses to specific pollutants as well as potentially ecological keystone species for monitoring programs (Perez, Blasco, & Sole, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among free radicals, reactive oxygen species such as hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH), and superoxide anion (O 2) are usually generated during cellular metabolism (Yuan, Chen, Zhou, Liu, & Yang, 2010). Hydroxyl radical is a neutral form from hydroxide ion and has a high reactivity, making it a very dangerous radical to the human cells (Du et al, 2017). Superoxide anion, a primary species of reactive oxygen species (ROS) function as a defense against viral or bacterial attack, also lead to damage of proteins, DNA, and lipid structures in human body (Tian, Mao, Okajima, & Ohsaka, 2005;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%